Continuous quality improvement (CQI) for cognitive skills in computer networking subject - Md Enzai, Nur Idawati; Rais, Siti Sara; Ab Ghani, Mohd Amir Hamzah; Ahmad, Norhayati; Mohamed, Syazilawati (Journal of Islamic, Social, Economics and Development, 2025)
Academicians worldwide have been implementing the Outcome-Based Education (OBE) approach to measure, monitor, and assess whether or not the Program Outcomes (POs) can be achieved in terms of developing the skills of the graduates. Faculty of Electrical Engineering (FKE) of Universiti Teknologi MARA Cawangan Terengganu (UiTMCT) uses a tool known as Course Outcome – Program Outcome (CO-PO) template to conduct PO measurement at the course level. The analysis results are then used for continuous quality improvement (CQI) tasks. This article focuses on an elective final year subject offered in FKE UiTMCT, Network Routing Fundamentals. For the year 2020 intake students, one PO out of three POs only achieved 53.5%, which is the cognitive skills-related PO. Though the attainment is over 50%, precautionary measures were taken for 2021 intake students to prevent the PO attainment from plummeting. For the year 2021 intake and year 2022 intake students, cognitive skills-related PO attainment increased to 76.9% and 68.5%, which also surpassed the Program Monitoring Level of 65%. This article explains the CQI activities conducted which is based on Plan-Do-Check-Act (PDCA) mechanism and analyses the related PO attainment results as well as outlining future actions.